Parental Self-Efficacy and Child Diet Quality between Ages 2 and 5: The STEPS Study - Tarro Saija; Lahdenperä Mirkka; Junttila Niina; Lampimäki Antti; Lagström Hanna (MDPI, 2022)
Parental self-efficacy (PSE), a measure of the subjective competence in the parental role, has been linked with child well-being and health. Research on the influence of PSE on child eating habits is scarce, and the few studies have concentrated on certain food groups, such as vegetables or fruits, and have mostly included only maternal PSE. Thus, the aim of this study was to explore the associations between PSE (separately for mothers and fathers and as a total family-level score) and child diet quality in a cross-sectional and longitudinal study setting. PSE was measured at child ages of 1.5 and 5 years, and diet quality was measured at ages 2 and 5. Participants are from the Steps to Healthy Development (STEPS) Study (n = 270−883). We found that maternal PSE and family level PSE score were associated with child diet quality. Paternal PSE was not, but the dimension Routines was associated with child diet quality. PSE was similarly associated with child diet quality at both age points. Our results suggest that PSE is an important construct in the development of healthy dietary habits in children, and supporting parenting programs aimed at higher PSE could promote healthy diet quality in children.